Qabūl ṭullāb PBA li-istikh¬dām al-dhikā’ al-iṣṭinā‘ī fī al-an-shitah al-akādīmiyyah istinādān ilā namūdhaj qabūl al-tiknūlūjiyā - Lulu Azka; Nur Laila Azizah; Naifah (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
The rapid development of Artificial Intelligence (AI) has transformed learning practices in higher education, including in Arabic Language Education (PBA). One emerging tool is Perplexity AI, which integrates AI-based search with real-time citation features that enable students to access academic sources more efficiently and verify information credibility. Despite its growing use, studies examining students’ acceptance of Perplexity in Arabic language learning remain limited. This study aims to analyze the acceptance of PBA students toward the use of Perplexity AI in academic activities using the Technology Acceptance Model (TAM). The research employed a qualitative descriptive approach with an exploratory case study design involving 20 PBA students selected through purposive sampling. Data were collected through open-ended questionnaires and analyzed thematically using NVivo. The findings indicate high levels of perceived usefulness and perceived ease of use. Around 90% of respondents reported that Perplexity helps accelerate task completion and improve understanding of Arabic learning materials, while 95% found the platform easy to use due to its intuitive interface. Students also demonstrated positive attitudes and strong behavioral intentions to continue using Perplexity, accompanied by awareness of ethical issues such as dependency and academic integrity.